Graphene-Carbon Nanotube Hybrids for Energy and Environmental Applications - Fan, Wei; Zhang, Longsheng; Liu, Tianxi (Springer Singapore : Imprint: Springer, 2017)
This book describes various carbon nanomaterials and their unique properties, and offers a detailed introduction to graphene-carbon nanotube (CNT) hybrids. It demonstrates strategies for the hybridization of CNTs with graphene, which fully utilize the synergistic effect between graphene and CNTs. It also presents a wide range of applications of graphene-CNT hybrids as novel materials for energy storage and environmental remediation. Further, it discusses the preparation, structures and properties of graphene-CNT hybrids, providing interesting examples of three types of graphene-CNT hybrids with different nanostructures. This book is of interest to a wide readership in various fields of materials science and engineering.
Keywords: Materials science.; Energy storage.; Electrochemistry.; Water pollution.; Nanotechnology.; elektronické knihy; electronic books